The isolated choice effect: An underlying psychological mechanism influencing racial diversity in organizations - Luo, Hanyang; Zhou, Wanhua; Song, Wugang (Frontiers in Psychology, 2022)
As a public health emergency of international concern, the outbreak of epidemic caused by the novel coronavirus (COVID-19) has greatly affected the global employment, especially the workforce diversity. We propose a feature of personnel administration that can unconsciously influence the racial diversity of organizations. We show that when making selections in isolation (i.e., when they are responsible for selecting a single person at a time), people are less likely to choose the one whose race would increase group diversity than when making selections in collections (i.e., when they are responsible for selecting several people at a time). Called the isolated choice effect, it provides a new insight on the challenges about why homogeneity persists in the workplace despite the public commitment of many well-intentioned organizations to increase diversity and inclusiveness as their social responsibility. Across eight experiments (n = 2,972), we demonstrate the importance of isolated choice effect in personnel selections and personnel layoffs. The details of questionnaires used in the experiments are shown in the supplementary materials. Our results show that people build a more race-diverse set when making combined choices and suggest that some organizational behavior management could be leveraged to help increase workforce diversity.